2010
DOI: 10.1007/s10528-010-9345-0
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome b Genetic Diversity and Maternal Origin of Chinese Domestic Donkey

Abstract: To clarify the origin of Chinese domestic donkeys, we investigated the mitochondrial Cytb gene from 244 animals from 13 native breeds. We found 55 variable sites in the Cytb gene sequence and subsequently defined 58 haplotypes. Analysis of haplotypes in combination with Cytb sequences revealed two mitochondrial origins in Chinese domestic donkeys, phenotypically expressed by the Somalian and Nubian lineages. The Somalian lineage predominated in Chinese domestic donkey breeds. Five specific Cytb gene SNPs diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…For He of the same single locus in comparable studies, Chinese donkeys were also similar to or slightly higher than European (Aranguren-Mendez et al 2001;Jordana et al 2001;Ivankovic et al 2002;Bordonaro et al 2012;Colli et al 2013) and American (Jordana et al 2015) donkeys. Those results were consistent with reports of previous mtDNA data on Chinese donkey breeds (Lei et al 2007;Zhang et al 2010).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For He of the same single locus in comparable studies, Chinese donkeys were also similar to or slightly higher than European (Aranguren-Mendez et al 2001;Jordana et al 2001;Ivankovic et al 2002;Bordonaro et al 2012;Colli et al 2013) and American (Jordana et al 2015) donkeys. Those results were consistent with reports of previous mtDNA data on Chinese donkey breeds (Lei et al 2007;Zhang et al 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Previous reports of Beja-Pereira et al (2004), Chen et al (2006), Lei et al (2007), Zhang et al (2010), and Perez-Pardal et al (2014) indicated a weak phylogeographic structure of indigenous donkey breeds by mtDNA studies. Using pedigree information, Gutierrez et al (2005) also suggested a weak population structure of indigenous Catalonian donkey breeds.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…; Zhang et al . ). However, mtDNA sequence variations reflect only the maternal contribution to the gene pool.…”
Section: Haplotypes Observed In 320 Donkeys and Their Distribution Frmentioning
confidence: 97%
“…It is a classical gene in nearly all eukaryotes and most prokaryotes, whose full length is about 1 100-1 200 bp, and is conserved among many species (Gray, 1989;. To date, the Cytb gene has been widely used in many phylogenetic and population genetic studies (Zhao et al, 2008;Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%